1996
DOI: 10.1093/jaoac/79.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Pesticide Residues in Human Milk, Soil, Water, and Food Samples Collectedfrom Kafr El-Zayat Governorate

Abstract: Pesticide residues in human milk and environmental samples from Kafr El-Zayat Governorate in Egypt were analyzed. This governorate is located near one of the biggest pesticide factories in Egypt. Organochlorine and organophosphorus pesticides were monitored, including those that have been prohibited from use in Egypt. Human milk samples (31 samples) from Kafr El-Zayat were compared with 11 samples collected from Cairo. Data were compared with results from studies performed in 1987 and 1990. The present study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…This fact explains the role of physicochemical properties of either diazinon or chlorpyrifos in their persistent in tissues or organic matter of sediment depending on heterocyclic contains (pyridine rings). Compounds detected in surface water were consistent with the fact that pesticides and fertilizers are the main products of the Kafr El-Zayat Company, and consistent with results of previous studies (Dogheim et al 1996; IPEN 2006; Abdel-Halim et al 2013; Abdel-Halim 2014). Those studies documented that organochlorine, organophosphorus, pyrethroid pesticides, PCBs, PAHs, and heavy metals were detected as by-products of industrial and urbanized activities in the Kafr El-Zayat region.…”
Section: Discussionsupporting
confidence: 91%
“…This fact explains the role of physicochemical properties of either diazinon or chlorpyrifos in their persistent in tissues or organic matter of sediment depending on heterocyclic contains (pyridine rings). Compounds detected in surface water were consistent with the fact that pesticides and fertilizers are the main products of the Kafr El-Zayat Company, and consistent with results of previous studies (Dogheim et al 1996; IPEN 2006; Abdel-Halim et al 2013; Abdel-Halim 2014). Those studies documented that organochlorine, organophosphorus, pyrethroid pesticides, PCBs, PAHs, and heavy metals were detected as by-products of industrial and urbanized activities in the Kafr El-Zayat region.…”
Section: Discussionsupporting
confidence: 91%
“…In rice grains, lindane content was considerably higher (20.2 and 37.5 mg·kg-1 ) (Mostafa 1987). DDT and lindane reached a slightly higher level compared to other or ganochlorine pesticides in such crops as spinach, potatoes, oranges, salad, and clover (Dogheim et al 1996). The study of the effect of DDT on the amino acid composition of cyanobacteria and green algae revealed that this pesticide affected the quality and quantity of the amino acid composition in the concentration-dependent manner (Czeczuga and Gierasimow 1977).…”
Section: Discussionmentioning
confidence: 93%
“…β-HCH is the most stable HCH isomer, it has slow elimination rate and thus has the tendency to accumulate in animal tissues over time as compared to other isomers [76] , [25] . Concentrations observed in this study were however the lowest amongst the assessed HCH isomers.…”
Section: Resultsmentioning
confidence: 99%